TPACK Integration Strategies in Elementary Mathematics Instruction - Marisa, Riandi; Santi, Yulia (Universitas Trunojoyo Madura, 2025)
This study explores the implementation strategies of the Technological Pedagogical Content Knowledge (TPACK) approach in elementary mathematics education. Using a qualitative case study design, the research examines how teachers integrate technological, pedagogical, and content knowledge in mathematics instruction. The study focuses on a sixth-grade teacher from a public elementary school in City X, selected based on their competency in educational technology. Data were collected through classroom observations, in-depth interviews, and analysis of teaching documents. Findings reveal that the TPACK strategy is implemented through three key aspects: (1) selection of relevant digital media, (2) development of technology-based interactive learning methods, and (3) design of activities connecting mathematical concepts to real-life contexts. The study identifies two critical success factors: teachers' ability to adapt to students' needs and their technological proficiency. The research concludes that the TPACK approach can enhance mathematics learning effectiveness in elementary schools when supported by continuous teacher training and adequate technological infrastructure. These findings contribute to understanding how technology integration can optimize pedagogical practices in basic education.